Global correlation of Cenomanian (Upper Cretaceous) sequences: Evidence for Milankovitch control on sea level - Gale, A; Hardenbol, J; Hathway, B; Kennedy, W; Young, JR; Phansalkar, V (2002)
We have investigated the sequence stratigraphy of two widely separated marine Cenomanian successions in southeast India and northwest Europe, and used high-resolution ammonite biostratigraphy to demonstrate that sea-level changes are globally synchronous and therefore must be eustatically controlled. Sequence-scale sea-level changes in the Cenomanian were driven by the long eccentricity cycle (400 k.y.) in the Milankovitch band. We hypothesize that, during pre-Quaternary time, the third-order sequences of Vail and Haq are essentially a sediment response to sea-level changes driven by the 400 k.y. cycle. Construction of a relative sea-level curve for the marginal marine succession in India demonstrates that the short-term sea-level changes are rapid (10-100 m/m.y.) and have a magnitude of 2-20 m. Glacioeustasy is a possible but unproven driving mechanism.